Graphene supported plasmonic photocatalyst for hydrogen evolution in photocatalytic water splitting - Singh, G. P.; Shrestha, K. M.; Nepal, A.; Klabunde, Kenneth J.; Sorensen, Christopher M. (My University, 2014)
It is well known that the noble metal nanoparticles show active absorption in the visible region because of the existence of the unique feature known as surface plasmon resonance (SPR). Here we report the effect of plasmonic Au nanoparticles on the enhancement of the renewable hydrogen (H2) evolution through photocatalytic water splitting. The plasmonic Au/graphene/TiO2 photocatalyst was synthesized in two steps: first the graphene/TiO2 nanocomposites were developed by the hydrothermal decomposition process; then the Au was loaded by photodeposition. The plasmonic Au and the graphene as co-catalyst effectively prolong the recombination of the photogenerated charges. This plasmonic photocatalyst displayed enhanced photocatalytic H2 evolution for water splitting in the presence of methanol as a sacrificial reagent. The H2 evolution rate from the Au/graphene co-catalyst was about 9 times higher than that of a pure graphene catalyst. The optimal graphene content was found to be 1.0 wt %, giving a H2 evolution of 1.34 mmol (i.e., 26 μmolhˉ¹), which exceeded the value of 0.56 mmol (i.e., 112 μmolhˉ¹) observed in pure TiO2. This high photocatalytic H2 evolution activity results from the deposition of TiO2 on graphene sheets, which act as an electron acceptors to efficiently separate the photogenerated charge carriers. However, the Au loading enhanced the H2 evolution dramatically and achieved a maximum value of 12 mmol (i.e., 2.4 mmolhˉ¹) with optimal loading of 2.0 wt% Au on graphene/TiO2 composites. The enhancement of H2 evolution in the presence of Au results from the SPR effect induced by visible light irradiation, which boosts the energy intensity of the trapped electron as well as active sites for photocatalytic activity.
Keywords: Graphene; TiO2; Hydrogen; Water-splitting